A Német Szövetség váltójogi jogalkotása és annak hatása az Osztrák Császárságra és a Magyar Királyságra - Baranyai, Marcell (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
Among the 19th century’s European legislative and codification processes nowadays’ jurisprudence is happy to highlight the creation of civil codes as a milestone in the development of civil law, however, we must not forget the flourishing of another, at least as important branch of private law: the commercial law. In parallel with the growth of overland and sea trade, with increasingly diversified commercial relations, commercial transactions developed, which may have served as a good basis for the development of private law. This study is the first in a series of commercial law history studies and presents the sources of different laws on bills of exchange in the German territories and the harmonizing legislation of the thousand-faced German Confederation, as well as its impact on the Austrian Empire, such as the Austrian law on bills of exchange and the Hungarian Kingdom's vicious, but ultimately rewarding independent legislative aspirations.